Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1159/000331470
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Exploration versus Intraoperative Endoscopic Sphincterotomy for Common Bile Duct Stones: A Prospective Randomized Trial

Abstract: Background/Aims: Laparoscopic cholecystectomy (LC) combined with intraoperative endoscopic sphincterotomy (IOES) was compared to LC with laparoscopic common bile duct exploration (LCBDE) to define the best single-session minimally invasive treatment for cholecystocholedocholithiasis. Methods: Between June 2009 and December 2010, patients with gallstones and common bile duct (CBD) stones diagnosed by preoperative ultrasonography and magnetic resonance cholangiopancreatography were randomized to LC-LCBDE or LC-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
2
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 77 publications
1
44
2
7
Order By: Relevance
“…Lauter and Froines [8] reported that 11 of 71 patients (15.5%) had retained stones after LCBDE. A more recent study reported that 4 of 115 patients (3.4%) had retained stones following LCBDE [22]. However, in our series, the rate of retained stones was 1.9% (3 of 157 patients), which was much lower than in previously published series.…”
Section: Discussioncontrasting
confidence: 91%
“…Lauter and Froines [8] reported that 11 of 71 patients (15.5%) had retained stones after LCBDE. A more recent study reported that 4 of 115 patients (3.4%) had retained stones following LCBDE [22]. However, in our series, the rate of retained stones was 1.9% (3 of 157 patients), which was much lower than in previously published series.…”
Section: Discussioncontrasting
confidence: 91%
“…Hong and colleagues randomized 234 patients with choledocholithiasis diagnosed by preoperative ultrasonography or IOC and found similar duct clearance rates for both groups: 89 per cent for the 141 patients having LBDE and 91 per cent for the 93 undergoing intraoperative endoscopic sphincterotomy. ElGeidie et al . randomized 226 patients with choledocholithiasis on IOC and similarly found no significant difference in duct clearance between the groups: 92 per cent in 112 patients in the LBDE group versus 97 per cent in 107 undergoing intraoperative endoscopic sphincterotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Only two previous studies have compared LBDE with intraoperative ERCP. Hong and colleagues randomized 234 patients with choledocholithiasis diagnosed by preoperative ultrasonography or IOC and found similar duct clearance rates for both groups: 89 per cent for the 141 patients having LBDE and 91 per cent for the 93 undergoing intraoperative endoscopic sphincterotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The oldest patients were a 96-year-old reported by Lee et al[10] and a 102-year-old reported in China[45]. In our study, 112 patients underwent LC (including 7 patients who underwent LC + EST/EPBD)[46,47], with a success rate of 100%, and none of the patients were converted to laparotomy. The key to success is management of indications and the opportunity to perform LC.…”
Section: Discussionmentioning
confidence: 79%